Sociodemographic and clinical profile of patients in voluntary and involuntary psychiatric hospitalizations - Carlos Robson Bezerra de Medeiros; Rafaella Maria Monteiro Sampaio; Jaina Bezerra de Aguiar; Francisco José Maia Pinto; Maria Selma Nogueira Oliveira (Universidade de Fortaleza, 2011)
Objective: To assess the sociodemographic and clinical profile of patients in psychiatric hospitalizations of voluntary inpatients (IPV) and involuntary (IPI), in psychiatric hospitals of Fortaleza-CE, Brazil, under contract with the Unified Health System (SUS). Methods: A quantitative study, descriptive, cross-sectional and analytical. The sample comprised 393 patients, distributed among 253 IPV and 140 IPI, submitted to Psychiatry specialtytreatment, in the year 2007. Results: For both patients, IPV and IPI, most were male: 185 (73.1%) and 82 (58.6%); single: 181 (46.7%) and 103 (26.5%); living in Fortaleza: 181 (71.5%) and 95 (67.9%), respectively, and aged 20 to 60 years (mean age of 37 years). Weobserved significant difference between the type of hospital and patient gender (p = 0.003), which did not occur with marital status (p = 0.688) and origin (p = 0.95). The main symptom profiles which justified the clinical admission of these patients were the use of alcohol or drugs 70 (27.6%), changes in critical judgments 40 (28.6%) and psychological distress 68 (26.9%). Family members were the main responsible for conducting these patients to the hospital. Conclusion: The results showed that patients on IPV and IPI, which joined in the study, had a socio-demographic and clinical profile characterized by: prevalence of male patients, from the capital Fortaleza, single, mean age of 37 years, having been brought tohospital by a relative, mainly due to alcohol use or drugs.